Silica dispersion, and abrasive material composition

The silica dispersion with controlled particle size and container design minimizes particle precipitation and aggregation, maintaining high surface quality of polished substrates.

JP2025008927APending Publication Date: 2025-01-20YAMAGUCHI SEIKEN IND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023111568
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Silica dispersions used in polishing processes can generate coarse particles during storage and transportation due to water evaporation, leading to scratches on polished surfaces.

Method used

A silica dispersion with average primary particle diameter between 3 to 100 nm, stored in a container with an inner spout wall made of organic polymer material and surface roughness of 60 nm or less, to prevent particle precipitation and aggregation.

Benefits of technology

Reduces the formation of coarse particles and scratches on polished surfaces, ensuring high surface quality of magnetic and semiconductor substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008927000001_ABST
    Figure 2025008927000001_ABST
Patent Text Reader

Abstract

To provide a silica dispersion capable of suppressing deposition of silica particles due to adhesion, dryness, and coagulation of the silica dispersion to an inner wall portion of a discharge port of a storage container and generation of coarse particles thereby capable of decreasing generation of scratch when an abrasive agent composition containing the silica dispersion is used.SOLUTION: The silica dispersion 1 is stored and / or transported in a state filled in a storage container 2, and contains silica particles 3 having an average primary particle diameter in the range of 3-100 nm and water 4, and the storage container 2 includes a container body 5 capable of filling the silica dispersion 1 and an outlet 6 joined to the container body 5 and formed of an organic polymer material, the surface roughness (Sa) of the inner wall portion 7b of the pouring outlet portion 6 in contact with the silica dispersion 1 is filled into the storage container 2 of 60 nm or less.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silica dispersion and an abrasive composition. More specifically, the present invention relates to a silica dispersion that is stored and / or transported in a state filled in a storage container, and an abrasive composition prepared using the silica dispersion. [Background technology]

[0002] Conventionally, in memory hard disk drives and the like, there has been a demand for further improvement in the recording density of the magnetic disk in order to increase the storage capacity and reduce the diameter of the magnetic disk, and therefore efforts have been made to increase the recording density by lowering the flying height of the magnetic head and reducing the unit recording area.

[0003] In the manufacture of magnetic disks, a polishing process for polishing the magnetic disk surface has been conventionally carried out, and high polishing accuracy in this polishing process, that is, high surface smoothness with as little unevenness (surface roughness) as possible on the magnetic disk surface after polishing, is required. In addition to high surface smoothness, it is also required to suppress the occurrence of waviness on the magnetic disk surface and the number of scratches that occur during polishing.

[0004] On the other hand, in the field of semiconductor manufacturing, there is an increasing demand for higher integration and higher speed. In particular, in order to achieve higher integration of semiconductor substrates, there is a demand for miniaturization, that is, for making the wiring constructed on the semiconductor substrate as thin as possible. In order to meet such demands, for example, in the manufacturing process of the semiconductor substrate, there is a demand for making the focal depth for exposing the photoresist as shallow as possible. Therefore, as with the above-mentioned magnetic disk, there is a demand for high smoothness of the substrate surface of the semiconductor substrate.

[0005] Thus, in order to obtain high surface smoothness on the magnetic disk surface of a magnetic disk or the substrate surface of a semiconductor substrate, it is particularly required to minimize the occurrence of scratches on the polished surface of the object to be polished (magnetic disk, etc.). For example, the use of a polishing composition containing colloidal silica has been proposed (see Patent Document 1).

[0006] Furthermore, an attempt has been proposed in which a silica dispersion used in a polishing liquid composition (or abrasive composition) or the like contains the above-mentioned colloidal silica as silica particles, and the silica dispersion is filtered in advance using a filter that uses a filter aid such as diatomaceous earth to remove coarse particles contained in the colloidal silica, thereby reducing the occurrence of scratches on the object to be polished even when used in a polishing process (see Patent Document 2).

[0007] When using the above-described polishing composition containing colloidal silica, a commercially available silica dispersion liquid is often used that is prepared in advance by stirring and mixing colloidal silica, water, and other additives at a prescribed mixing ratio, and an acid and an oxidizing agent are added to such a silica dispersion liquid to prepare an abrasive composition, which is then used in the polishing step.

[0008] In the manufacturing process of silica dispersion liquid, the silica dispersion liquid is stored in a storage container after production, and is transported to the shipping destination in the same state. Therefore, it may take a certain period of time (for example, several months to about six months) from the time the silica dispersion liquid is produced until it is used in the polishing process. As a result, there is a possibility that a part of the water contained in the stored silica dispersion liquid evaporates depending on the temperature around the storage container. Even if the storage container is filled with the silica dispersion liquid to nearly the specified capacity, a gas phase portion (gas phase portion) that contacts the liquid surface of the silica dispersion liquid exists near the outlet on the top side of the storage container.

[0009] As a result, the silica dispersion in the stored and / or transported state may adhere to the inner surface of the storage container at a position facing the gas phase, particularly to the inner wall of the spout provided on the upper surface of the storage container. As a result, some water may evaporate from the adhered silica dispersion, causing silica particles such as colloidal silica contained in the silica dispersion to precipitate from the adhered inner wall. Furthermore, the precipitated silica particles may aggregate, generating larger coarse particles.

[0010] When silica particles or the like are precipitated on the inner wall, when the silica dispersion is moved from the storage container to the outside, that is, when the silica dispersion is poured out, solid silica particles or coarse particles are discharged to the outside of the storage container together with the liquid silica dispersion, and the coarse particles or the like may be mixed in the silica dispersion.When the silica dispersion mixed with such coarse particles or the like is used as the raw material of an abrasive composition, the hard coarse particles with large particle diameter may cause scratches on the surface of the object to be polished.In other words, the storage state may affect the surface quality after the polishing process.

[0011] In response to this, in order to set the filling rate of the abrasive particle dispersion (silica dispersion) filled in the container higher than usual, the ratio of the contact area of ​​the abrasive particle dispersion to the total area of ​​the inner wall surface of the container is set to a specified value or higher (see Patent Document 3). This reduces the occurrence of nano-scratches and makes it possible to manufacture magnetic disk substrates and the like with excellent surface quality. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2002-327170 A [Patent Document 2] JP 2014-124766 A [Patent Document 3] JP 2006-130638 A Summary of the Invention [Problem to be solved by the invention]

[0013] However, the above-mentioned silica dispersions containing colloidal silica may have the following problems: As described above, evaporation of a part of the water contained in the silica dispersion during storage or transportation may result in the generation of coarse particles, which may cause scratches.

[0014] In addition, as shown in Patent Document 3, there is a physical limit to specifying the ratio of the liquid contact area within a prescribed range and increasing the filling rate, and in particular, at least a part of the inner wall of the outlet of the storage container for filling and pouring out the silica dispersion liquid, etc., is in contact with the gas phase. As a result, water evaporates from the silica dispersion liquid, etc., adhering to the inner wall of the outlet of the storage container, and the silica particles, such as colloidal silica, dry and aggregate, so that coarse particles may still be generated from the silica particles.

[0015] In view of the above circumstances, the present invention focuses on a storage container used for storing and / or transporting a silica dispersion, and has an object to provide a silica dispersion and an abrasive composition that can suppress adhesion of the silica dispersion to the inner wall of the spout of the storage container, drying, precipitation of silica particles, and generation of coarse particles due to aggregation of silica particles, thereby reducing the occurrence of scratches when an abrasive composition containing the silica dispersion is used. [Means for solving the problem]

[0016] Means for Solving the Problems The inventors of the present application have conducted extensive research into the above problems and have developed the following silica dispersion and abrasive composition, and have found that the above problems can be solved.

[0017] [1] A silica dispersion which is stored and / or transported in a filled state in a storage container, the silica dispersion containing silica particles having an average primary particle diameter in the range of 3 to 100 nm and water, the storage container comprising a container body capable of being filled with the silica dispersion, and a pouring outlet part joined to the container body, at least an inner wall part of which is formed of an organic polymer material, the silica dispersion filled in the storage container having a surface roughness (Sa) of 60 nm or less of the inner wall part of the pouring outlet part which comes into contact with the silica dispersion during storage and / or transport.

[0018] [2] The silica dispersion according to [1], wherein the silica particles are colloidal silica.

[0019] [3] The silica dispersion according to [1], wherein the organic polymer material is a polyethylene resin or a polypropylene resin.

[0020] [4] The silica dispersion according to [1] above, having a pH value (25°C) of 7 or more.

[0021] [5] The silica dispersion according to [1], wherein the surface roughness (Sa) of the inner wall portion is 35 nm or less.

[0022] [6] A polishing agent composition comprising the silica dispersion according to any one of the above [1] to [5], an acid and / or a salt thereof, and an oxidizing agent. Effect of the Invention

[0023] The silica dispersion of the present invention can suppress the precipitation of silica particles and the generation of coarse particles during storage and / or transportation, and by using an abrasive composition using the silica dispersion, scratches and the like are reduced, and magnetic disk substrates, semiconductor substrates, and the like with excellent surface conditions can be obtained. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is an explanatory diagram showing a schematic configuration of a storage container with a lid to be filled with a silica dispersion according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing the schematic configuration of the spout part of the storage container with the lid removed. [Diagram 3] FIG. 2 is an explanatory diagram showing the relationship between the liquid level, the inner wall, and the gas phase of the silica dispersion near the pouring outlet of a storage container with a lid attached. [Figure 4] FIG. 2 is an explanatory diagram showing a schematic diagram of the state of deposition of silica particles and generation of coarse particles on the inner wall of the spout portion, and the measurement position of the surface roughness (Sa) of the inner wall. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The following describes the embodiments of the present invention. However, the present invention is not limited to the following embodiments. It should be understood that modifications and improvements made to the following embodiments based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention are also within the scope of the present invention.

[0026] 1.Silica dispersion A silica dispersion 1 according to one embodiment of the present invention can be stored and / or transported in a state filled in a storage container 2 (details of which will be described later), and contains at least silica particles 3 having an average primary particle diameter in the range of 3 to 100 nm and water 4, which are mixed in a predetermined blending ratio.

[0027] More specifically, the silica dispersion 1 of this embodiment can use well-known silica particles such as colloidal silica or fumed silica as the silica particles 3. In particular, it is preferable to use colloidal silica in order to reduce the amount of scratches on the disk surface when used as an abrasive composition. Note that the silica particles 3 constituting the silica dispersion 1 may be one or a combination of the above colloidal silica, fumed silica, etc.

[0028] Here, colloidal silica that is preferably used as the silica particles 3 in the silica dispersion 1 of this embodiment can be obtained by, for example, a water glass method in which an alkali metal silicate such as sodium silicate is used as a raw material and a condensation reaction is carried out in an aqueous solution to grow particles; an alkoxysilane method in which an alkoxysilane such as tetraethoxysilane is used as a raw material and a condensation reaction is carried out in water containing a water-soluble organic solvent such as alcohol to obtain colloidal silica; or a method in which metallic silicon is reacted with water in the presence of an alkali catalyst to produce colloidal silica while generating hydrogen gas.

[0029] On the other hand, fumed silica that can be used as the silica particles 3 can be obtained by a gas phase method or the like in which a volatile silicon compound such as silicon tetrachloride is used as a raw material and grown by hydrolysis at a high temperature of 1000° C. or higher using an oxygen-hydrogen burner. The structures of these colloidal silica, fumed silica, and the like are conventionally well known, and these can be used as appropriate.

[0030] The silica particles 3 used in the silica dispersion 1 of this embodiment have an average primary particle diameter (D50) in the range of 3 to 100 nm, and more preferably in the range of 5 to 80 nm for the purposes of suppressing aggregation of the silica particles 3 themselves, making the surface roughness of the object to be polished (e.g., a magnetic disk, etc.) uniform, and reducing scratches generated on the surface of the object to be polished (such as the surface of a magnetic disk, etc.).

[0031] Here, various shapes of silica particles 3 are known, for example, spherical, non-spherical, chain-like, confetti-like, etc., and are not particularly limited in the silica dispersion of the present invention. However, in order to reduce the occurrence of scratches, as described below, it is preferable to use silica particles that are spherical or close to spherical.

[0032] Furthermore, the ratio of the silica particles 3 and the water 4 in the silica dispersion 1 is not particularly limited, but for example, by setting the silica concentration in the silica dispersion 1 in the range of 0.5 to 50 mass%, more preferably in the range of 1.0 to 45 mass%, the storage stability of the silica dispersion 1 itself can be improved, and the occurrence of scratches on the object to be polished when the silica dispersion 1 is used in an abrasive composition can be reduced.

[0033] Here, the pH value (25°C) of the silica dispersion 1 can be set arbitrarily, but from the viewpoints of the dispersion stability of the silica particles 3 in the silica dispersion 1 and reducing the occurrence of scratches on the polished object described above, the pH value (25°C) is preferably 7 or more.More preferably, the pH value can be 8 or more, and more preferably 9 or more.

[0034] On the other hand, from the viewpoint of suppressing dissolution of the silica particles 3 in the silica dispersion 1, the pH value (25° C.) is preferably 12 or less, more preferably 11 or less.

[0035] As described above, by adjusting the type of silica particles 3, the range of the average primary particle size (D50) of the silica particles 3, the shape of the silica particles 3, the silica concentration in the silica dispersion 1, and the pH value (25° C.) of the silica dispersion 1 within appropriate ranges, it is possible to obtain an excellent silica dispersion 1 that is excellent in the dispersion stability and dissolution inhibition of the silica particles 3 and that can suppress the occurrence of scratches when used in an abrasive composition.

[0036] 2.Storage container The storage container 2 used for filling, storing and / or transporting the silica dispersion liquid prepared as described above is mainly composed of a container body 5 and a pouring outlet part 6 joined to the upper surface side of the container body 5, as shown in the schematic configuration in Figures 1 to 4.

[0037] Here, Figure 1 is an explanatory diagram showing the schematic configuration of a storage container 2 with a lid attached to be filled with a silica dispersion 1 of one embodiment of the present invention, Figure 2 is an explanatory diagram showing the schematic configuration of the pouring outlet 6 of the storage container 2 with the lid removed, Figure 3 is an explanatory diagram showing the relationship between the liquid level 1a of the silica dispersion 1, the inner wall 7b, and the gas phase 11 in the vicinity of the pouring outlet 6 of the storage container 2 with the lid attached, and Figure 4 is an explanatory diagram showing typically the state of precipitation of silica particles 3 on the inner wall 7b of the pouring outlet 6 and the generation of coarse particles 12, and the measurement positions P1, P2, and P3 of the surface roughness (Sa) of the inner wall 7b.

[0038] The outlet 6 of the storage container 2 filled with the silica dispersion 1 of this embodiment further includes an outlet body 7 having a substantially cylindrical shape, and a lid 10 having a female screw portion 9 formed on the inside of the lid (not shown) that can be screwed with a male screw portion 8 that protrudes in a spiral shape from the outer wall portion 7a of the outlet body 7 (see FIG. 1 or FIG. 3). As a result, the lid 10 can be fastened and fixed to the outlet 6 by screwing the female screw portion 9 of the lid 10 into the male screw portion 8 of the outlet 6, and the silica dispersion 1 filled inside the container body 5 can be sealed. As a result, the silica dispersion 1 does not leak from the storage container 2 during storage and / or transportation.

[0039] Furthermore, in the pouring outlet 6 of the storage container 2, at least the inner wall portion 7b located on the inner periphery side of the pouring part main body 7 is formed of an organic polymer material. The inner wall portion 7b of the pouring part main body 7 is formed of a smooth curved surface, and the surface roughness (Sa) of the inner wall portion 7b is set to be 60 nm or less. That is, the silica dispersion 1 of this embodiment is characterized in that it is filled in a storage container 2 having an inner wall portion 7b with a surface roughness (Sa) of 60 nm or less, and is stored and / or transported.

[0040] More specifically, the storage container 2 filled with the silica dispersion 1 of this embodiment has the entire pouring outlet 6 formed of a polyolefin resin material such as polyester resin or polypropylene resin. More specifically, the storage container 2 is composed of a container body 5 formed by joining a plurality of semi-transparent soft sheets made of a polyolefin resin material into a substantially cubic shape, and the pouring outlet 6 and lid 10 formed of a white hard material made of a polyolefin material.

[0041] Here, since the container body 5 of the storage container 2 is formed of a soft sheet material, the container body 5 itself has a property of being easily deformable against stress. Therefore, when the container body 5 is not filled with the silica dispersion 1, it can be stored in a small folded state, while when the container body 5 is filled with the silica dispersion 1, it can adopt a shape such as a substantially cubic shape as shown in Fig. 1. That is, the storage container 2 used to fill the silica dispersion 1 of this embodiment can be a so-called "flexible container" whose shape can be arbitrarily deformed according to the filling amount of the silica dispersion 1 or the like into the container body 5.

[0042] The storage container 2 is not limited to the configuration shown in Figure 1 etc., and may be, for example, one having a cardboard outer shell that further covers the outer surface of the container body 5 formed from the above-mentioned organic polymer material, or a composite container in which the container body 5 is made of a metal material such as a metal can, a metal drum, or a metal container, and only the spout portion 6 and the lid portion 10 are made of an organic polymer material.

[0043] Furthermore, the organic polymer material constituting the pouring outlet 6 etc. of the storage container 2 and the container body 5 is not particularly limited, and may be a material other than the polyolefin-based resin material such as the above-mentioned polyethylene resin or polypropylene resin. However, in consideration of various conditions such as low affinity with the silica particles 3, difficulty in adhering to the silica particles 3, being widely distributed in the market, ease of availability, and cost, the above-mentioned polyethylene resin or polypropylene resin is particularly preferable.

[0044] The polyethylene resin can be low-density polyethylene (LDPE) produced by a high-pressure method using a radical polymerization initiator, copolymer-type linear low-density polyethylene (LLDPE) produced by a low-pressure method using a metallocene catalyst, or homopolymer-type high-density polyethylene (HDPE) produced by a low-pressure method using a Ziegler catalyst.

[0045] On the other hand, examples of polypropylene resins include broad molecular weight distribution polypropylene obtained using a Ziegler-Natta catalyst, and narrow molecular weight distribution polypropylene obtained using a metallocene catalyst.

[0046] These exemplified polyethylene resins and polypropylene resins may be homopolymers or copolymers with different monomers, and examples of the polyethylene resin include homopolymer high-density polyethylene resins, ethylene-butene copolymerized polyethylene resins, hexene-based linear low-density polyethylene resins, etc. Examples of the polypropylene resin include propylene homopolymers, random copolymers in which ethylene, butene, etc. are randomly copolymerized with propylene, and block copolymers in which ethylene and propylene are randomly copolymerized after propylene homopolymerization, etc.

[0047] When filling the container body 5 of the storage container 2 with the silica dispersion 1, there is a limit to the filling rate even if the filling amount of the silica dispersion 1 is increased or the air in the void portion in the storage container 2 where the silica dispersion 1 is not contained is removed to increase the filling rate as much as possible (the ratio of the liquid contact area of ​​the silica dispersion 1 to the total area of ​​the inner wall surface of the storage container 2). Therefore, as shown in Fig. 3, at least a gas phase portion 11 is formed between the liquid level 1a of the silica dispersion 1 and the lid back surface 10a of the lid portion 10 that is screwed into the pouring outlet portion 6 and seals the storage container 2.

[0048] When the silica dispersion 1 is stored or transported in a state filled in the storage container 2, the liquid surface 1a may shake due to vibration or the like, and a part of the silica dispersion 1 filled may adhere to the inner wall 7b of the outlet 6. Then, water 4 evaporates from the silica dispersion 1 adhered to the inner wall 7b, causing silica particles 3 to precipitate on the inner wall 7b. At this time, the precipitated silica particles 3 may aggregate with each other and be generated as coarse particles 12 having a large particle size (see FIG. 4). Note that, for ease of explanation, FIG. 4 shows an enlarged view of the vicinity of the outlet 6 with the lid 10 removed, and shows the silica particles 3 and coarse particles 12 adhered to the inner wall 7b in a schematic manner.

[0049] When the silica dispersion 1 is to be used for an abrasive composition or the like in this state in which the silica particles 3 have precipitated on the inner wall portion 7b and coarse particles 12 have been generated, the storage container 2 with the lid portion 10 removed is lifted and tilted to pour out the silica dispersion 1 from the spout portion 6.

[0050] At this time, the silica particles 3 precipitated on the inner wall portion 7b of the outlet portion 6 and the generated coarse particles 12 are discharged to the outside of the storage container 2 together with the pouring out of the silica dispersion liquid 1. As a result, there is a possibility that a problem occurs in which scratches are generated on the surface (disk surface, etc.) of the polished object (magnetic disk, etc.) after polishing.

[0051] Therefore, the storage container 2 for filling the silica dispersion 1 of this embodiment is characterized in that the pouring outlet 6 is formed from at least an organic polymer material, which suppresses the precipitation of the silica particles 3 in the silica dispersion 1 and the generation of coarse particles 12 as much as possible, and the surface roughness (Sa) of the inner wall portion 7b of the pouring outlet 6 is set to 60 nm or less.

[0052] Furthermore, it is desirable that the surface roughness (Sa) of the inner wall 7b is preferably 35 nm or less, more preferably 25 nm or less. In this way, by setting the surface roughness (Sa) of the inner wall 7b of the outlet 6 to 60 nm or less, even if a part of the silica dispersion 1 temporarily remains on the inner wall 7b as droplets or a liquid film due to a liquid level fluctuation caused by a temperature change during storage or vibration during transportation, such droplets or a liquid film quickly descend along the inner wall 7b and are taken into the silica dispersion 1. As a result, the silica dispersion 1 and the polishing agent composition formed using the silica dispersion 1 are not mixed with coarse particles 12 made of colloidal silica or the like, and the occurrence of scratches during polishing of the polished object can be reduced.

[0053] Here, the lower limit of the surface roughness (Sa) of the inner wall 7b of the spout 6 of the storage container 2 is not particularly limited, but considering the releasability from the mold used in molding the spout 6 and the handleability, for example, the surface roughness (Sa) of the inner wall 7b is preferably set to 5 nm or more, more preferably 10 nm or more. If the surface roughness (Sa) of the inner wall 7b is set to less than 5 nm, the adhesion between the spout 6 and the mold after molding increases, making it difficult to remove it from the mold. In other words, problems with releasability may occur, reducing work efficiency or imposing an excessive burden on the worker.

[0054] The surface roughness (Sa) of the inner wall 7b of the outlet 6 of the storage container 2 can be arbitrarily controlled by the type of organic polymer material such as polyethylene resin or polypropylene resin used as the raw material, the surface roughness (Sa) of the mold itself when molding using the organic polymer material, the material temperature of the organic polymer material filled in the mold, or the pressure inside the mold during molding, etc. These controls are well known in the resin molding technology, so a detailed description will be omitted here.

[0055] Furthermore, the molding of the spout portion 6 can be performed using a conventionally known resin molding technique, such as injection molding, blow molding (hollow molding), sheet molding, and film molding, and any of these can be selected depending on the type of organic polymer material used and the shape of the spout portion 6. The spout portion 6 can be formed in a single molding process, or can be formed by molding a plurality of parts separately and combining and joining these parts.

[0056] In addition, the organic polymer material used as the raw material for the container body 5, the spout 6, and the lid 10 constituting the storage container 2 can be the above-mentioned polyethylene resin or the like as a main raw material, and additives such as antioxidants, ultraviolet absorbers, antistatic agents, antibacterial agents, fillers, colorants, lubricants, and flame retardants may be blended into the main raw material. The blending of these additives is well known in the technical field of resin molding processing, and detailed explanations will be omitted.

[0057] Furthermore, a release agent may be used to facilitate the removal of the spout 6 molded using a mold. This reduces the surface roughness (Sa) of the inner wall 7b of the spout 6 to suppress the generation of coarse particles 12, making it difficult to remove the spout 6 from the mold. Even if this makes it difficult to remove the spout 6 from the mold, the release agent can be applied to the spout 6 to allow the spout 6 to be removed quickly from the mold, preventing a decrease in work efficiency and reducing the burden on the worker. The release agent and application method used may be any of those well known in the art.

[0058] 3. Abrasive composition The polishing compound composition (not shown) according to one embodiment of the present invention can be prepared using as a raw material the above-mentioned silica dispersion 1. That is, the polishing compound composition can be composed of the silica dispersion 1, an acid and / or a salt thereof, and an oxidizing agent.

[0059] As an example, in the case of an abrasive composition used for polishing a nickel-phosphorus plated aluminum magnetic disk, it is preferable to use silica dispersion 1 whose pH has been adjusted to be acidic. Here, the pH value (25° C.) of the abrasive composition is preferably set to 0.1 to 4.0, more preferably 0.5 to 3.0.

[0060] The pH of the polishing compound of this embodiment can be adjusted by appropriately adding the following acid and / or its salt. The silica dispersion 1 filled in the storage container 2 is preferably mixed with the acid and / or its salt immediately before use as the polishing compound, and it is preferable to store the acid and / or its salt separately in an acid-resistant container such as a bottle different from the silica dispersion 1 until mixing begins.

[0061] Specific examples of acids and / or salts thereof that can be used in the polishing compound composition of this embodiment include inorganic acids and salts thereof such as nitric acid, sulfuric acid, nitrous acid, persulfuric acid, hydrochloric acid, perchloric acid, phosphoric acid, phosphonic acid, phosphinic acid, pyrophosphoric acid, tripolyphosphoric acid, and amidosulfuric acid, 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, and ethylenediaminetetra(methylenephosphonic acid). Examples of suitable phosphonic acids include organic phosphonic acids such as ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, and α-methylphosphonosuccinic acid, and salts thereof, aminocarboxylic acids such as glutamic acid and aspartic acid, and carboxylic acids such as oxalic acid, nitroacetic acid, and maleic acid, and salts thereof. Among the above-listed acids, inorganic acids, organic phosphonic acids, and salts thereof are particularly preferable from the viewpoint of reducing scratches.

[0062] The polishing compound of the present embodiment may further contain an oxidizing agent. Usable oxidizing agents include peroxides, persulfuric acid or its salts, permanganic acid and its salts, chromic acid and its salts, peroxoacid and its salts, and mixtures of two or more of these oxidizing agents.

[0063] More specifically, examples of the compounds include hydrogen peroxide, sodium peroxide, barium peroxide, potassium peroxide, potassium permanganate, metal salts of chromate, metal salts of dichromate, persulfuric acid, sodium persulfate, potassium persulfate, ammonium persulfate, peroxolinic acid, and sodium perborate. Among the compounds listed above, hydrogen peroxide, persulfuric acid and salts thereof are particularly preferred, and hydrogen peroxide is more preferred.

[0064] The content of the oxidizing agent in the polishing composition of this embodiment is preferably 0.01 to 10.0 mass %. Furthermore, the polishing composition may contain other components that are conventionally known, as necessary. For example, a thickener, a dispersant, a rust inhibitor, a surfactant, etc. may be added.

[0065] The polishing compound composition of this embodiment can be used in a process for polishing a substrate to be polished, for example, by supplying the above-mentioned polishing compound composition between a polishing platen having a polishing pad attached thereto and a substrate to be polished, and moving the polishing platen and / or the substrate to be polished under a predetermined polishing pressure.

[0066] Examples of materials suitable for polishing with the polishing agent composition of this embodiment include metal materials such as silicon, aluminum, nickel, tungsten, tantalum, titanium, etc., semimetals, or alloys thereof, as well as glass, alumina, silicon dioxide, and silicon nitride. In particular, the polishing agent composition of this embodiment is suitable for polishing objects containing metals such as aluminum, nickel, and tungsten, or alloys mainly composed of these metals. For example, it is suitable for polishing nickel-phosphorus plated aluminum alloy substrates and glass substrates such as crystallized glass and reinforced glass, and is particularly suitable for polishing nickel-phosphorus plated aluminum alloy substrates.

[0067] Furthermore, when a plurality of polishing steps are set in the manufacture of a magnetic disk substrate or the like, the polishing composition of this embodiment is preferably applied to at least the second or subsequent steps. That is, in order to reduce scratches and surface roughness and obtain excellent surface smoothness, it is suitable to apply it to a finish polishing step (final polishing step). EXAMPLES

[0068] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples, and it goes without saying that the present invention can be embodied in various forms as long as it falls within the technical scope of the present invention. In the following, the storage container 2 and the like will be appropriately described using the reference numerals attached to Figs. 1 to 4.

[0069] (1) Preparation of silica dispersion The silica dispersions used in Examples 1 to 3 and Comparative Example 1 all use silica particles (colloidal silica) with a primary average particle size (D50) of 28 nm, are adjusted so that the concentration of silica particles (silica concentration) in the silica dispersion is 30 mass %, and have a pH value (25° C.) of 10.0. Details of the method for measuring the primary average particle size (D50) of silica particles (colloidal silica) will be described later (see "Method for measuring particle size of colloidal silica").

[0070] (2) Storage container The storage containers 2 (A, B, C, D) used in Examples 1 to 3 and Comparative Example 1 to be filled with the silica dispersions can be those shown in Figures 1 to 4 already described, and are flexible containers with an internal volume of 10 liters, in which the container body 5 is made of sheet-like low-density polyethylene (LDPE), and the pouring outlet part 6 provided on the upper surface of the container body 5 and the lid part 10 that can be screwed onto the pouring outlet part 6 are each made of hard high-density polyethylene (HDPE).

[0071] Four types of storage containers A, B, C, and D are prepared, each having a different surface roughness (Sa) of the inner wall portion 7b of the spout portion 6. The surface roughness (Sa) value indicates the average value of the measurement results at three measurement positions P1, P2, and P3 on the inner wall portion 7b shown in Figure 4, based on the "surface roughness measurement method" described later.

[0072] Here, the surface roughness (Sa) of storage container A in Example 1 is 17.0 nm, similarly the surface roughness (Sa) of storage container B in Example 2 is 31.4 nm, the surface roughness (Sa) of storage container C in Example 3 is 40.7 nm, and the surface roughness (Sa) of storage container D in Comparative Example 1 is 68.3 nm (see Table 1). In other words, only storage container D in Comparative Example 1 is out of the range of surface roughness (Sa) of inner wall portion 7b of spout portion 6 of storage container 2 defined in the present invention.

[0073] (3) Filling storage containers and storing The silica dispersion 1 prepared by the above (1) is filled into storage containers A, B, C, and D having different surface roughness (Sa) of the inner wall portion 7b of the spout portion 6. Here, the silica dispersion 1 is filled into the storage container A etc. so that the ratio of the liquid contact area of ​​the silica dispersion 1 to the total area of ​​the inner wall surface of the storage container 2 having a specified internal volume of 10 liters (=filling rate) is 99%. Then, the storage container 2 after being filled with the silica dispersion 1 is stored in a room where the room temperature is kept between 10 and 30°C for 3 months and 6 months in a stationary state.

[0074] As described above, by filling the silica dispersion 1 so that the liquid contact area ratio is 99%, as shown in Figure 3, the liquid level 1a of the silica dispersion 1 reaches the vicinity of the inner wall portion 7b of the spout portion 6, and a small gas phase portion 11 is formed between the liquid level 1a and the lid back surface 10a of the lid portion 10 screwed onto the spout portion 6.

[0075] (4) Preparation of abrasive composition The silica dispersions stored in the storage containers A, B, C, and D for 3 and 6 months were poured out from the outlet 6 and diluted with pure water to prepare a polishing composition having a colloidal silica concentration of 4.0% by mass. The prepared polishing composition contained 0.8% by mass of sulfuric acid as an acid and 0.8% by mass of hydrogen peroxide as an oxidizing agent in addition to the silica dispersions and water after storage. The pH value (25°C) of the prepared polishing composition was 1.2.

[0076] (5)Measuring method, polishing conditions (5-1) Colloidal Silica Particle Size Measurement Method The primary average particle diameter (D50) of the silica particles (colloidal silica) used in Examples 1 to 3 and Comparative Example 1 was measured by the following measurement method: A transmission electron microscope (TEM) (JEM2000 (200 kV) manufactured by JEOL Ltd.) was used to photograph the object (silica particles) at a magnification of 100,000 times, and the photographed image was analyzed using image analysis software (Mac-View Ver. 4.0 manufactured by Mountec Co., Ltd.) to measure the Heywood diameter (diameter equivalent to a circle with a projected area).

[0077] The average primary particle size (D50) of colloidal silica was determined by analyzing the particle sizes (Heywood size) of approximately 2,000 colloidal silica particles using the above-mentioned measurement method, and calculating the particle size at which the cumulative particle size distribution (accumulated volume basis) from the small particle size side is 50% using the above-mentioned image analysis software.

[0078] (5-2) Surface roughness measurement method Using a three-dimensional optical profiler (New View 8300, manufactured by AMETEK Co., Ltd.), the surface roughness (Sa) of the inner wall 7b of the spout 6 was measured under the measurement conditions of "x50 lens," "x2.0 image zoom," and "measurement field of view: 80 μm x 80 μm." As described above, the surface roughness (Sa) was measured at three measurement positions P1, P2, and P3 shown in Figure 4, and the average of the measured values ​​at each of the measurement positions P1, P2, and P3 was calculated to obtain the surface roughness (Sa).

[0079] (5-3) Evaluation of adhesion and adhesion state of silica particles and coarse particles After storage for 3 and 6 months in the storage container 2, the lid 10 was removed from the spout 6, and the presence and state of adhesion of silica particles 3 or coarse particles 12 to the inner wall 7b of the spout 6 was visually confirmed.

[0080] (5-4) Polishing conditions The object to be polished (piece to be polished) was an electroless nickel-phosphorus plated aluminum alloy magnetic disk substrate having an outer diameter of 97 mm, which had been roughly polished in advance. This was then finish-polished using the abrasive compositions prepared according to the polishing conditions described below. Polishing machine: Speedfam Co., Ltd., 9B double-sided polishing machine Polishing pad: P2 pad manufactured by FILWEL Co., Ltd. Rotation speed of surface plate: Upper surface plate -8.3min -1 Lower surface plate 25.0min -1 Abrasive composition supply rate: 100ml / min Polishing time: 300 seconds Processing pressure: 11kPa

[0081] (5-5) Scratch measurement conditions after polishing The surface of the disk substrate after the polishing in (5-4) above was observed using a scratch measuring device (MicroMAX VMX-4100 manufactured by Vision Cytec Co., Ltd.), and the number of scratches on the substrate surface was counted. Tilt angle: -5° Magnification: 20x The measurement was performed under the following measurement conditions. Here, the scratch ratio is shown as a relative value when the number of scratches when polishing is performed using the polishing composition using the silica dispersion before being filled into the storage container, i.e., the silica dispersion immediately after preparation, is taken as 1 (reference value). Here, the number of scratches caused by the polishing composition using the silica dispersion before being filled into the storage container was 0.30 / side. That is, when 10 substrate surfaces after polishing were observed, 3 scratches were confirmed.

[0082] (6) Summary of measurement results The measured surface roughness (Sa) and scratch ratio due to polishing are shown in Table 1 below.

[0083] [Table 1]

[0084] (7) Consideration When the silica dispersion was stored using the storage container D of Comparative Example 1 having a relatively high surface roughness (Sa) of 68.3 nm, significant precipitation and adhesion of silica particles 3 and generation and adhesion of coarse particles 12 were visually observed on the inner wall 7b of the outlet 6 of the storage container D after 6 months. Then, using each of the silica dispersions after 3 months and 6 months of storage, polishing compositions were prepared and polishing tests were carried out. As a result, as shown in Table 1 above, it was found that the scratch ratio of the substrate surface was 5.80 after 3 months of storage and 10.20 after 6 months of storage, which was significantly increased compared to immediately after filling.

[0085] In contrast, when the storage container A of Example 1, in which the surface roughness (Sa) of the inner wall portion 7b is 17.0 nm, was used, the deposition and adhesion of the silica particles 3 on the inner wall portion 7b after 6 months, and the generation and adhesion of the coarse particles 12 were hardly observed by visual inspection, and the scratch ratio was 1.00 after 3 months of storage and 1.01 after 6 months of storage, with little increase. In other words, it was confirmed that the storage container A of Example 1 was hardly affected by storage.

[0086] On the other hand, when the storage container B of Example 2, in which the surface roughness (Sa) of the inner wall portion 7b is 31.4 nm, was used, the deposition and adhesion of the silica particles 3 on the inner wall portion after 6 months, and the generation and adhesion of the coarse particles 12 were not so much when visually confirmed, and the scratch ratio was 1.13 after 3 months of storage and 1.24 after 6 months of storage. When the storage container C of Example 3, in which the surface roughness (Sa) of the inner wall portion 7b is 40.7 nm, was used, the deposition and adhesion of the silica particles 3 on the inner wall portion 7b after 6 months of storage, and the generation and adhesion of the coarse particles 12 were slightly confirmed by visual confirmation, and the scratch ratio was 3.52 after 3 months of storage and 6.84 after 6 months of storage.

[0087] That is, as the surface roughness (Sa) of the inner wall portion 7b increases, the deposition and adhesion of the silica particles 3 and the generation and adhesion of the coarse particles 12 tend to increase, and it was confirmed that the scratch ratio of the substrate surface after the polishing test also increases accordingly. However, compared to the case where the storage container D of Comparative Example 1 was used, in the cases of the storage containers B and C of Examples 2 and 3, the increase in the scratch ratio after 6 months of storage was not so large, and it was confirmed that there was no practical problem.

[0088] As explained above, by controlling the surface roughness (Sa) of the inner wall of the spout of the storage container used for filling, storing and / or transporting the silica dispersion to a predetermined value or less, i.e., by making the surface roughness (Sa) 60 nm or less, it is possible to suppress the precipitation and adhesion of silica particles and the generation and adhesion of coarse particles to the inner wall, and even when the resulting mixture is subsequently used as a raw material for an abrasive composition, good surface quality can be maintained without an increase in scratches. [Industrial Applicability]

[0089] The silica dispersion of the present invention and the polishing agent composition using the same can be used for polishing various electronic parts such as semiconductors, SAW devices, magnetic recording media, and ceramic parts such as oxides. In particular, it can be suitably used for polishing the surface of substrates for magnetic recording media such as glass magnetic disk substrates and aluminum magnetic disk substrates. Furthermore, it can be suitably used for polishing aluminum magnetic disk substrates for magnetic recording media, which have an electroless nickel-phosphorus plating film formed on the surface of an aluminum alloy substrate. [Explanation of symbols]

[0090] 1: silica dispersion, 1a: liquid surface, 2, A, B, C, D: storage container, 3: silica particles, 4: water, 5: container body, 6: spout, 7: spout body, 7a: outer wall, 7b: inner wall, 8: male thread, 9: female thread, 10: lid, 10a: back of lid, 11: gas phase, 12: coarse particles, P1, P2, P3: measurement positions.

Claims

1. A silica dispersion that is stored and / or transported in a state filled in a storage container, Silica particles having an average primary particle size in the range of 3 to 100 nm; Water and Contains The storage container comprises: A container body capable of filling the silica dispersion therein; a pouring outlet portion joined to the container body, at least an inner wall portion of which is made of an organic polymer material; Equipped with The silica dispersion filled in the storage container has an inner wall portion of the spout portion that comes into contact with the silica dispersion during storage and / or transportation having a surface roughness (Sa) of 60 nm or less.

2. The silica particles are 2. The silica dispersion according to claim 1, which is a colloidal silica.

3. The organic polymer material is 2. The silica dispersion according to claim 1, which is a polyethylene resin or a polypropylene resin.

4. 2. The silica dispersion according to claim 1, having a pH value (25° C.) of 7 or more.

5. 2. The silica dispersion according to claim 1, wherein the surface roughness (Sa) of the inner wall portion is 35 nm or less.

6. A silica dispersion according to any one of claims 1 to 5, an acid and / or a salt thereof; Oxidizing agent and 1. An abrasive composition comprising:

Citation Information

Patent Citations

  • Polishing liquid composition

    JP2002327170A

  • Encased abrasive material particle dispersed liquid

    JP2006130638A

  • Method for producing polishing liquid composition

    JP2014124766A